Characteristics of cervical cancer screening using visual inspection with acetic acid and pap smear in the outpatient clinic at Prof. Dr I.G.N.G. Ngoerah Hospital Denpasar from January to December 2023 - Aryana, Made Bagus Dwi; Surya, I Gede Ngurah Harry Wijaya; Winata, I Gde Sastra; Ongko, Eric Gradiyanto; Budiana, Nyoman Gede; Mahendra, I Nyoman Bayu; Saspriyana, Kade Yudi; Darmayasa, I Made; Prayudi, Pande Kadek Aditya (Indonesian Journal of Perinatology, 2025)
Introduction: According to GLOBOCAN 2022, cervical cancer is the fourth leading cause of cancer-related morbidity and mortality among women worldwide, with 662,044 new cases and 348,709 deaths. In Southeast Asia, it ranks third in incidence and fourth in mortality. Indonesia contributes more than 50% of new cases (36,964) and deaths (20,708) in the region. Cervical cancer is largely preventable through early detection methods such as visual inspection with acetic acid (VIA) and Pap smear. However, differences in diagnostic accuracy between these screening methods highlight the need to identify patient characteristics appropriate for each modality. This study aimed to compare the characteristics of patients undergoing VIA and Pap smear screening at the outpatient clinic of Prof. Dr I.G.N.G. Ngoerah Hospital, Denpasar, from January to December 2023. Methods: This observational analytical study used secondary data obtained from outpatient clinic registers and medical records of female patients who underwent VIA or Pap smear screening during the study period. Data were analysed using univariate analysis. Results: Among 122 participants undergoing VIA, 24 (19.6%) had positive results. Pap smear examinations in 125 participants showed CIN I in 10 (8.0%), CIN II in 4 (3.2%), and CIN III in 5 (4.0%) participants. Vaginal discharge was reported in 7 VIA participants (5.7%) and 15 Pap smear participants (12.0%), while postcoital bleeding was reported in 2 participants (1.6%) in each group. Among VIA-positive cases, lesions were most commonly found in all four quadrants (45%). Conclusion: Patient characteristics in VIA and Pap smear screening at Prof. Dr I.G.N.G. Ngoerah Hospital varied considerably, with a higher proportion of positive results observed in VIA compared to Pap smear screening.